(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe nutrition status and the quality of life non-small cell lung cancer patients before chemotherapy at Vietnam National Cancer Hospital. Materials and methods: A cross-sectional study was conducted on 95 patients with non-small cell lung cancer before chemotherapy at Vietnam National Cancer Hospital from January 2024 to November 2024. Results: According to PG-SGA, sixty percent of patients diagnosed with stage B and stage C. Average overall health score 70.88±23.47, average functional score 80.21±21.21, average symptom score 23.33±20.65 and financial burden score 27.37±35.39. Significantly, the patients under 60 years old had the lowest quality of life (p<0.05). As a result, patients were well-nourished, and quality of life scores significantly increased. Conclusion: A large number of patients with non-small cell lung cancer before chemotherapy are undernutrition, and quality of life score is above average. Additionally, more attention should be paid to the quality of life of lung cancer patients under 60 years old.